Pengaruh VUCA (Volatility, Uncertainty, Complexity, Ambiguity) dan Transformasi Digital Terhadap Efektivitas Organisasi (Studi Pada Staf PT Nyalindung) - Rezza Oktaviani; Maman Suratman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the impact of VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) and Digital Transformation on Organizational Effectiveness at PT Nyalindung. This research employs a quantitative method with a total sample of 60 permanent employees selected using a census sampling technique. Data were collected through literature study, interviews, and questionnaires. The data were analyzed using multiple linear regression analysis with the assistance of SPSS statistical software. The results of the study show that the level of VUCA at PT Nyalindung is categorized as moderately high, Digital Transformation is categorized as high, while Organizational Effectiveness is categorized as poor. The partial test results indicate that VUCA has a negative and significant effect on Organizational Effectiveness. Meanwhile, Digital Transformation has a positive and significant effect on Organizational Effectiveness. Furthermore, the simultaneous test results reveal that VUCA and Digital Transformation together have a significant influence on Organizational Effectiveness. These findings imply that increasing levels of VUCA tend to reduce organizational effectiveness, whereas well-implemented digital transformation contributes positively to enhancing organizational effectiveness